Complete Genome Sequences of pLMA1 and pLMA7, Two Large Linear Plasmids of Micrococcus Strains Isolated from a High-Altitude Lake in Argentina - Dib, Julian Rafael; Perez, María Florencia; Schuldes, Jörg; Poehlein, Anja; Wagenknecht, Martin; Farías, María E.; Meinhardt, Friedhelm; Daniel, Rolf (Genome announcements (Washington, DC), 2018)
The two linear plasmids pLMA1 (109,112 bp) and pLMA7 (82,075 bp) from Micrococcus strains were isolated from a high-altitude lake in the Argentinean Puna, sequenced, and annotated. These extrachromosomal elements are probably conjugative and harbor genes potentially involved in coping with the harsh conditions in such extreme environments.